The Influence of Perceived Convenience, Perceived Usefulness, and Perceived Risk on the Use Of QRIS to Increase MSMEs Income - Fauziah, Indah; Yuliyanti, Dini; Maula, Nida Syarofatul; Destiana, Rina (International Journal of Business, Law, and Education, 2024)
QRIS (Quick Response Code Indonesia Standard) is a national standard for payments using QR codes in Indonesia. QRIS was developed by Bank Indonesia and the Indonesian Payment System Association (ASPI) to facilitate and unify various digital payment methods through standard QR codes. This study discusses the effect of perceived ease of use, perceived usefulness, and perceived risk on the use of QRIS to increase MSME income. There are 100 samples used and the sampling technique is through purposive sampling technique and the PLS-SEM method as the analysis with SmartPLS. The results of the study state that perceived ease of use, perceived usefulness have a significant influence on the use of QRIS while perceived usefulness has an insignificant influence on the use of QRIS. And the use of QRIS has a significant effect on MSME income.